Respuesta :

Answer: 9

To solve this, you'd first have to substitute the values of x and y. Since x=6 and y=1, all you have to do is plug them in.

Equation:  (1)3+6

Next, all you have to do is solve. Since 3(1)=3, and 6+3=9, the value of the expression is equal to 9.

**Unless the 3 is an exponent. It didn't look like it to me but I solved that as well just in case***

Equation: y³+x

1. Substitute

(1)³+6

2. Solve

1³= 1 and 1+6=7

So, the answer is 7 (again, this is only if the 3 is an exponent. I couldn't tell)...

Hope this helps,

LaciaMelodii :)